VALUATION OF INVESTMENT ATTRACTIVENESS OF THE PROJECT FOR THE PRODUCTION METHANOL IN RUSSIA - D. V. Voyko; A. G. Berg (Вестник университета)
The issues of assessing the investment attractiveness of the project for the production of methanol in Russia have been considered. A model for calculating the internal rate of return and evaluating the investment project for the methanol industry has been proposed. The developed investment project evaluation model includes preparation of forecast information, identification and analysis of internal trends of the company, formation of project reports, as well as financial justification for calculating the internal rate of return. The investment attractiveness of a typical large-capacity methanol plant has been carried out, the main key factors affecting operating flows have been revealed. The assessment perfomed has showedthe high potential of methanol production projects in Russia.